Optimum yearly and seasonal tilt angle of solar system in the center of Babylon/Iraq using PVsyst software - Mohanad Aljanabi; Muhammed Salah Sadiq Al-Kafaji; Ahmed Hussein Duhis (Institute of Advanced Engineering and Science, 2023)
The photovoltaic system tilt angle is one of the more significant factors for obtaining the maximum solar energy that will fall on the PV panel. Consequently, then obtain maximum power output, the solar array needs to be angled properly. The analysis for a stand-alone system is simulated and modelled using PVsyst software version-7.2 for system power 3,120 Wp to obtain the optimum value of the tilt angles of maximum solar irradiation in the center of Babylon Governorate, Iraq. The ideal tilt angle for the south has been found for both yearly and the seasons. Different tilt angles were taken which were (29°, 30°, and 31°) annually, azimuth angle for all is (0°). The incident global irradiation in the collector plane, Incident beam irradiation in the collector plane is maximum at tilt angle (29°) that produces maximum available energy 5,132 kWh/kWp/year. same processing for annual different tilt angle was taken for seasonally; the results show that the angle (49°) for summer and (13°) for winter are the optimum tilt angle which obtains the maximum incident global irradiation in the collector plane, maximum incident beam irradiation in the collector plane at this angle then product maximum available energy 5,343 kWh/kWp/year.